A Deep understanding of the value of external audit for internal control and stakeholders - Muhammad Rafly; Handayani, Monika (Fakultas Ekonomi dan Bisnis, Universitas Palangka Raya (UPR), 2025)
This research aims to gain a deep understanding of the value of external audits for internal controls and stakeholder trust by analyzing relevant previous journals. The approach used in this research is a literature study, which collects and analyzes various findings from previous research on the role of external audits in improving the effectiveness of internal controls and strengthening stakeholder trust. The results of the study show that external audits play an important role in ensuring the sustainability of a strong internal control system, as well as increasing the credibility of financial reports, which has a positive impact on stakeholder trust.